Hemoglobin - Ahmad Ibrahim (My University, 2023)
In this time in which we live, technology has become a part of everything around us, and for this it was necessary to search for an idea to link technology to the subject of medical laboratories. I present to you this project for medical laboratories, which is a smart phone application that patients can use and benefit from in several goals, such as access to the nearest medical laboratory from your location, and also enables you to book an appointment to go to the laboratory in order to save time, and you can also get your examination result without the need to return to the laboratory Once again, and also to know the prices of medical examinations. Also, this application helps the laboratory staff to know who made the reservation for them, and enables them to send the results to them and access the patient record. Flutter programming language was used to build this project, and because it is considered as a cross platform framework we used it for both the mobile application and the website. NodeJS was used to build the server, and MongoDB was used for database utilization.